Ming Qing zhi ji "da xue" quan shi yan jiu - Chen, Qun 1985- (Ke xue chu ban she, 2017)
Abstract
Anm.
Keywords: Geschichte 1368-1911; Da xue; Chinese classics / Study and teaching / China; Chinese classics / History and criticism; Chinese classics; Chinese classics / Study and teaching; Ru jia; Literatur; Universität; Chinesisch; Klassiker; China